2013
DOI: 10.1120/jacmp.v14i2.4141
|View full text |Cite
|
Sign up to set email alerts
|

Intrafraction displacement of prone versus supine prostate positioning monitored by real‐time electromagnetic tracking

Abstract: Implanted radiofrequency transponders were used for real‐time monitoring of the intrafraction prostate displacement between patients in the prone position and the same patients in the supine position. Thirteen patients had three transponders implanted transperineally and were treated prone with a custom‐fitted thermoplastic immobilization device. After collecting data from the last fraction, patients were realigned in the supine position and the displacements of the transponders were monitored for 5–7 minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A full bladder has been shown to reduce inter-fraction setup error when compared to an empty bladder [10], although difficulty maintaining a consistent bladder volume has been reported in the literature. Nakamura et al [11] and O'Doherty et al [12] both observed inconsistent bladder volume during the course of radiotherapy when using a full bladder protocol, whilst irregular prostate motion has been attributed to both bladder filling and patient movement [13]. Previous studies have also investigated the impact of rectal diameter on prostate motion [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A full bladder has been shown to reduce inter-fraction setup error when compared to an empty bladder [10], although difficulty maintaining a consistent bladder volume has been reported in the literature. Nakamura et al [11] and O'Doherty et al [12] both observed inconsistent bladder volume during the course of radiotherapy when using a full bladder protocol, whilst irregular prostate motion has been attributed to both bladder filling and patient movement [13]. Previous studies have also investigated the impact of rectal diameter on prostate motion [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…4,11 Our previous work has shown that obese patients are tracked just as accurately as nonobese men, 12 and that patients may be monitored in either the prone or supine position. 13 Currently, the manufacturer does not recommend implantation of transponders in patients with a hip prosthesis due to concerns that metallic hip material may interfere with electromagnetic tracking of the transponders. To our knowledge this has not been validated in the setting of a peer-reviewed study but is instead argued on a theoretical basis.…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation of our study is that 3D–translations of the prostate gland were simulated, which may or may not reflect the motion experienced by the whole gland and the vesicles [ 25 ]. Further, we have disregarded intra-fraction motion, which may vary (marginally) for supine and prone positioning [ 26 ]. In addition, potential rotations or deformations were not included in the simulation model.…”
Section: Discussionmentioning
confidence: 99%